Tourism and its Associated Aspects in the River Island Majuli, Assam: A Study from the Perspective of Visitors - Konwar, Jecob; Chakraborty, Deb Kr. (Prabandhan: Indian Journal of Management, 2015)
The tourism industry, with an impressive growth rate across the world, is no doubt one of the fastest growing industries. Tourism is the largest sector in the worldwide export of goods and services, and accounts for 12% of the total global income. This paper intended to highlight differences in opinion among respondents before and after visiting the river island Majuli. Majuli is one of the potential tourist destinations of North-East India, and the approach towards the tourism industry needs a substantial upliftment, and focus needs to be placed on the community-based tourism model. To achieve positive results, efforts need to be made by the local authorities and communities so that visitors' word of mouth recommendations open new doors for prospective visitors.